2017
DOI: 10.1103/physrevb.96.180415
|View full text |Cite
|
Sign up to set email alerts
|

Dirac-surface-state-dominated spin to charge current conversion in the topological insulator ( Bi0.22Sb0.78)2Te3

Abstract: We report the spin to charge current conversation in an intrinsic topological insulator (TI) (Bi0.22Sb0.78)2Te3 film at room temperature. The spin currents are generated in a thin layer of permalloy (Py) by two different processes, spin pumping (SPE) and spin Seebeck effects (SSE).In the first we use microwave-driven ferromagnetic resonance of the Py film to generate a SPE spin current that is injected into the TI (Bi0.22Sb0.78)2Te3 layer in direct contact with Py. In the second we use the SSE in the longitudi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 69 publications
(132 reference statements)
3
29
1
Order By: Relevance
“…The conversion from spin current to charge current, inverse Edelstein effect, of the Bi 2 Se 3 -based topological insulators has been studied via spin pumping from either ferromagnetic metallic layer or ferromagnetic insulators. [78][79][80][81][82][83] Beyond Bi 2 Se 3 -based topological insulators, recent theoretical and experimental studies have identified new topological insulators, such as α-Sn and strongly correlated Kondo insulator SmB 6 . For α-Sn thin films, theoretical calculations show that α-Sn thin films could be topological insulators via strain or quantumsize effects.…”
Section: Spin and Charge Conversion In Topological Insulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion from spin current to charge current, inverse Edelstein effect, of the Bi 2 Se 3 -based topological insulators has been studied via spin pumping from either ferromagnetic metallic layer or ferromagnetic insulators. [78][79][80][81][82][83] Beyond Bi 2 Se 3 -based topological insulators, recent theoretical and experimental studies have identified new topological insulators, such as α-Sn and strongly correlated Kondo insulator SmB 6 . For α-Sn thin films, theoretical calculations show that α-Sn thin films could be topological insulators via strain or quantumsize effects.…”
Section: Spin and Charge Conversion In Topological Insulatorsmentioning
confidence: 99%
“…76,86,87,93,96 Up to date, a large range of the spin and charge efficiency values from~0.001 to~2 has been reported for the topological insulators, using different techniques including ST-FMR, spin pumping and inverse Edelstein effect, magnetization switching, and second harmonic measurement, etc. 66,[69][70][71][72][78][79][80][81][82][83]87,97,98 Even for the same measurement on the same topological insulator, i.e., second harmonic measurement of the spin-orbit torque arising from 3D topological insulators, different values have been reported. 70,99 One possible reason is related to the multiple sources of second harmonic voltages, i.e., large unidirectional magnetoresistance is also reported at the topological insulator/FM interface.…”
Section: Spin and Charge Conversion In Topological Insulatorsmentioning
confidence: 99%
“…Topological insulators (TIs) provide a fascinating example where strong spin–orbit interaction leads to the formation of spin‐momentum‐locked (topological) surface states, and are anticipated to mediate superior spin–charge interconversion . As a result, employing conventional steady‐state transport set‐ups, TIs have been exploited to exert spin orbit torque on the adjacent ferromagnetic (FM) layers, as well as generate charge current from spin current . However, these transport studies involved contact fabrication, required complicated data analysis to extract the spin‐related component, and their signal is in the DC regime.…”
mentioning
confidence: 99%
“…14 Hence, we here suggest that the spin-to-charge conversion in our Py/Cu/TI system arises from inverse Edelstein effect, where the origin is the spin-momentum locked surface states of TI layer, same interpretation as other literatures. 5,11 Low G eff ¯ indicates strong spin back ow and spin memory loss (spin absorption) at the high SOC interface. 16,17 .…”
Section: Spin Mixing Conductance G Effmentioning
confidence: 99%
“…5,6,7,8 Numerous studies have been reported for determining the spin-to-charge conversion e ciency in 3D TI. 5,9,10,11 Particularly, giant spin hall angle (SHA) as large as ∼0.43 was reported in Bi 2 Se 3 that attributed to the enhanced spin current by the surface states and then converted into dc-voltage due to the bulk inverse spin hall effect. 9 However, large variations of SHA was found, which is an order of magnitude difference and the authors ascribed such variation to the non-uniformity of interface quality.…”
Section: Introductionmentioning
confidence: 99%